Maintenance Management Damage Prevention on the Twin Shaft Concrete Mixer at PT. X - Heru Winarno; Muhammad Rizaldi Fauzan Aprilianto (International Journal of Applied Research and Sustainable Sciences, 2023)
PT. Waskita Beton Precast, Tbk is a company that manufactures precast and ready mix concrete with the largest production currently. Producing various high quality concrete with international standards, such as spun pile, full slab, box girder and others. Problems in maintaining production facilities must be considered to maintain quality and increase productivity. When the machine and its components experience damage, the production process can be hampered or even stopped. The purpose of this researchhow is the maintenance management carried out by the companyIn industrial companies, one of the maintenance that must be paid attention to is the maintenance of the machines they own. There are several types of maintenance systems that can be implemented, including: after-breakdown maintenance systems, routine maintenance systems, re-maintenance systems and productive maintenance systems. However, there are times when a component/machine should be replaced based on operating hours in accordance with the manufacturer's instructions to avoid greater losses